Otomatisasi Eksperimen Interferensi Tiga Celah - Albertus Hariwangsa Panuluh; Elisabeth Dian Atmajati; Sri Agustini Sulandari (Lambung Mangkurat University Press, 2020)
Automation of three slit interference experiments has been carried out. The light interference is an interesting phenomenon to observe. The observation of the three-slit interference pattern uses a light sensor that is connected to the computer through the interface. Light intensity data will be directly recorded into the computer and displayed in the form of graphs of the light intensity versus time. To measure the pattern of the formed dark light, the light sensor is placed on a linear drive system. This drive system will move the sensor to the left or right to record the intensity of the pattern of dark light. The purposes of this study are: 1) designing an automatic experiment to observe three slit interference patterns and 2) measuring the wavelength of the light source, He-Ne laser, used in the experiment. From the experiment, we find that the wavelength of He-Ne laser is nm.